Beneficial effects of a woman-focused development programme on child survival: evidence from rural Bangladesh - Bhuiy, Abbas; Chowdhury, Mushtaque (Social Science and Medicine, 2019)
This paper reports results from a prospective study of the impact of a woman-focused development programme on child survival in Matlab, a rural area of Bangladesh. The programme was targeted to households owning less than 50 decimals of land and members selling more than 100 days of labour for living in a year. Programme components included formation of women's groups for saving and credit, training on skill development, functional literacy including legal and social awareness, and technical and marketing support to projects undertaken with the loan money from the organization. A total of 13,549 children born alive during 1988–97 in the study area were included in the study. Hazards of mortality during pre- and post-intervention periods were compared among the programme participants and non-participants controlling the effects of other relevant variables. There has been a substantial reduction in mortality during the post-intervention period; however, the reduction was much greater for infants whose mothers participated in the development programme compared to infants of non-participant mothers from similar socioeconomic background. In a relative sense, there has been a 52% reduction of the pre-intervention level hazard of death of children during infancy of participant mothers compared to 31% reduction for the infants of non-participant mothers from similar socioeconomic background. There had also been a substantial reduction in hazard of death during childhood (1–4 year age group), however, the reduction was statistically similar for all groups of children irrespective of their mothers’ participation in the development programmes.